Exploring nurses' perception about the care needs of patients with COVID-19: a qualitative study - Nasrin Galehdar; Tahereh Toulabi; Aziz Kamran; Heshmatolah Heydari (BMC, 2020)
Abstract Background COVID-19 is a new disease affecting and killing a large number of people across the world every day. One way to improve health care for these patients is to recognize their needs. Nurses, as a large population of health care staff, can be rich sources of information and experience on patients' care needs. Therefore, the aim of this study was to explore nurses' perception about the care needs of patients with COVID-19. Methods The present qualitative research was performed using the conventional content analysis approach in Iran from March to May 2020. The participants of this study included the nurses caring for patients with COVID-19, recruited by the purpose sampling method. The data was collected through 20 telephone interviews and analyzed based on the method proposed by Lundman and Graneheim. Results Qualitative data analysis revealed six main categories including need for psychological consulting, need for quality improvement of services, need for upgrading of information, need for improving of social support, need for spiritual care and need for social welfare. Conclusion The data showed that patients with COVID-19 were psychologically, physically, socially, economically, and spiritually affected by the disease. Therefore, they should be comprehensively supported by health care staff and other supportive systems.